The madness of vision : on baroque aesthetics - Buci-Glucksmann, Christine (Series in Continental thought, 2013)
This is a study of phenomenological aesthetics of the baroque. Integrating the work of Merleau-Ponty with Lacanian psychoanalysis, Renaissance studies in optics, and twentieth-century mathematics, the author asserts the materiality of the body and world in her aesthetic theory. All vision is embodied vision, with the body and the emotions continually at play on the visual field. Thus vision, once considered a clear, uniform, and totalizing way of understanding the material world, actually dazzles and distorts the perception of reality. In each of the nine essays that form this text, the author develops her theoretical argument via a study of a major painting, sculpture, or influential visual image - Arabic script, Bettini's "The Eye of Cardinal Colonna," Bernini's Saint Teresa and his 1661 fireworks display to celebrate the birth of the French dauphin, Caravaggio's Judith Beheading Holofernes, the Paris arcades, and Arnulf Rainer's self-portrait, among others - and deftly crosses historical, national, and artistic boundaries to address the work of Gracián; Monteverdi's opera Orfeo; the poetry of Hafiz, John Donne, and Baudelaire; as well as baroque architecture and Anselm Kiefer's Holocaust paintings. In doing so, the author makes the case for the pervasive influence of the baroque throughout history and the continuing importance of the baroque in contemporary arts. --